2022
DOI: 10.3390/insects13080676
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitocidal Activity of the Methanolic Extract of Annickia chlorantha and Its Isolated Compounds against Culex pipiens, and Their Impact on the Non-Target Organism Zebrafish, Danio rerio

Abstract: In this study, the crude extract and its isolated compounds from the stem bark of Annickiachlorantha were tested for their larvicidal, developmental, and repellent activity against the mosquito vector, Culex pipiens, besides their toxicity to the non-target aquatic organism, the zebrafish (Danio rerio). The acute larvicidal activity of isolated compounds; namely, palmatine, jatrorrhizine, columbamine, β-sitosterol, and Annickiachlorantha methanolic extract (AC), was observed. Developmentally, the larval durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Using insecticides to control agricultural pests may lead to important risks for non-target aquatic organisms (Ba et al, 2018). Previous studies have shown that the methanolic extract of Annickia chlorantha had mosquitocidal activity, and a very low toxic effect on on the non-target organism D. Rerio (Selim et al, 2022). Our research aligns with these ndings, the RHE was practically nontoxic to D. rerio compared to the toxicity of M. neustria testacea larvae reported here.…”
Section: Discussionsupporting
confidence: 89%
“…Using insecticides to control agricultural pests may lead to important risks for non-target aquatic organisms (Ba et al, 2018). Previous studies have shown that the methanolic extract of Annickia chlorantha had mosquitocidal activity, and a very low toxic effect on on the non-target organism D. Rerio (Selim et al, 2022). Our research aligns with these ndings, the RHE was practically nontoxic to D. rerio compared to the toxicity of M. neustria testacea larvae reported here.…”
Section: Discussionsupporting
confidence: 89%
“…Zetasizer software (V7.12, Malvern Instruments, Malvern, UK) was used to collect and evaluate data. The mosquito Culex pipiens larvae were colonized as previously described by Selim et al [51]; they were provided ad libitum with fish food as a diet and maintained at laboratory conditions of 27 ± 2 • C, 70 ± 5% relative humidity (RH), with a 14-10 h photoperiod. The housefly Musca domestica (L.) adults were fed on a mixture of sugar and milk powder (1:1).…”
Section: Characterization Of Biosynthesized Zno-npsmentioning
confidence: 99%